Non-Pharmacological Therapy to Reduce Pain Intensity in Patients - Nasrun Pakaya; Hartono Hadjarati; Widy Susanti Abdulkadir; Edy Dharma Putra Duhe; Gusti Pandi Liputo (Jurnal Kesehatan Masyarakat, 2025)
Pain is still the main problem for patients being treated in the treatment room. To overcome pain, analgesic drugs are often given. Even though the first step to help reduce pain can be to use non-pharmacological therapy. This study aims to see effect of non pharmacological therapy in reducing patient pain levels. The type of research is a quasi experiment with a one-group pre-test and post-test design approach. Sampling using accidental sampling technique over a period of 1 month obtained 50 respondents who matched the characteristics of the respondents in the research. Overall non- pharmacological therapy (beson relaxation, murotal, guide imagery, zikr, warm compresses, and hypnosis techniques) can reduce pain intensity in respondents who experience pain. Pain management in patients does not always involve immediate administration of medication. Non-pharmacological measures must always be prioritized to treat pain. Non-pharmacological therapy has been proven to be able to overcome or reduce pain levels.